2013
DOI: 10.1007/s11605-012-2092-2
|View full text |Cite
|
Sign up to set email alerts
|

Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy (ALPPS): Tips and Tricks

Abstract: The presented technique was feasible and safe in the hands of experienced hepatobiliary surgeons, with satisfactory short-term results. It induces rapid liver hypertrophy and at the same time it offers the possibility of cure to patients previously declared unresectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0
20

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(184 citation statements)
references
References 19 publications
3
161
0
20
Order By: Relevance
“…10 In the present series, we again report no deaths within 90 days in 32 patients, which to our knowledge makes this study the largest single-centre cohort with no perioperative mortality. 4 The largest available studies reporting on short-term outcomes of ALPPS are analyses of the International ALPPS Registry, with a published 90-day mortality of 9% and a severe complication (Clavien-Dindo ≥ IIIb) rate of 27%. 8,9 This morbidity and mortality is further attenuated in patients with CRLM and in those older than 60 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In the present series, we again report no deaths within 90 days in 32 patients, which to our knowledge makes this study the largest single-centre cohort with no perioperative mortality. 4 The largest available studies reporting on short-term outcomes of ALPPS are analyses of the International ALPPS Registry, with a published 90-day mortality of 9% and a severe complication (Clavien-Dindo ≥ IIIb) rate of 27%. 8,9 This morbidity and mortality is further attenuated in patients with CRLM and in those older than 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…The second stage follows with removal of the deportalized part of the liver after rapid hypertrophy of the FLR. 4 The mechanism behind the accelerated hypertrophy in ALPPS is yet to be fully understood. Schlegel and colleagues 5 described an elegant rodent study suggesting that the rapid hypertrophy of liver parenchyma may be associated with a systemic increase of circulating factors released as part of an inflammatory reaction to the parenchymal split in conjunction with portal vein ligation (PVL) and increased blood flow to the FLR.…”
mentioning
confidence: 99%
“…At the same time, Schadde et al reported that the mortality were 11% (CI=8%-16%) and 44% (CI=38-50) respectively with complications grade IIIa or higher. On the contrary, Alvarez et al obtained 0% mortalities under modifications in highly selected patients, and the morbidity was decreased to 36% by Hernandez-Alejandro et al 4,22,23 Many surgeons payed special attention to the tumor recurrence and overall survival. Schadde et al compared 48 ALPPS cases with 83 conventional-staged hepatectomies cases, and found that the tumor recurrence at 1 year was 54% versus 52% for ALPPS and PVE/PVL, respectively (p=0.7).…”
Section: The Safety and Short-term Outcomes Of Alppsmentioning
confidence: 99%
“…The pathologies that ALPPS is commonly used to treat include colorectal liver metastases, hilar cholangiocarcinoma, and HCC. Contraindications for ALPPS include unresectable liver metastases in the FLR, unresectable extrahepatic metastases, severe portal hypertension, high anesthetic risks, and a poor condition prior to major surgery (53).…”
Section: Associating Liver Partition and Pvl For Staged Hepatectomy (mentioning
confidence: 99%